Standing at work and varicose veins - Tüchsen, Finn; Krause, Niklas; Hannerz, Harald; Burr, Hermann; Kristensen, Tage S. (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'This study attempts to determine whether or not prolonged standing at work involves an excess risk for the occurrence of varicose veins.' ' METHODS ': 'A cohort of 1.6 million 20-to-59-year-old Danes gainfully employed in 1991 were followed for 3 years according to first hospitalization due to varicose veins of the lower extremities. The exposure data came from a representative sample of the baseline population. Altogether 5940 people were interviewed about occupational exposure and confounding factors.' ' RESULTS ': 'For men working mostly in a standing position, the risk ratio for varicose veins was 1.85 [95% confidence interval (95% CI) 1.33-2.36] when compared with all other men. The corresponding risk ratio for women was 2.63 (95% CI 2.25-3.02). The results were adjusted for age, social group, and smoking.' ' CONCLUSIONS ': 'Working in a standing position is associated with subsequent hospitalization due to varicose veins for both men and women.
Keywords: epidemiology; hospitalization; prospective study; record linkage; varicosis; venous insufficiency